Differences in the effect of 40%-glucose on the optical properties of healthy and stromal-sarcoma ovaries in cats - Selifonov, Aleksey A. (Journal of biomedical photonics & engineering)
Differences in diffuse reflectance and total transmittance of healthy and sarcoma cat ovarian tissue were determined using integrating sphere spectroscopy and confirmed by histological analysis. The effective diffusion coefficient determined from the analysis of the kinetics of the diffuse reflectance was found equal to D = (7.5 ± 0.9)10-7 cm2/s for healthy tissue and D = (1.4 ± 0.2)10-6 cm2/s for sarcoma. In healthy tissue, optical clearing occurred with the formation of two UV transparency windows: (18 ± 4) nm wide centered at 225 nm and (50 ± 12) nm wide centered at 375 nm. For the ovary with sarcoma, the formation of only one transparency window centered at 380 nm and a width of (43 ± 11) nm was observed. © 2023 Journal of Biomedical Photonics & Engineering.